The Relevances between Poda Na Lima Philosophy with Islamic Perspective - Iskandarsyah Siregar; Ramlan Siregar (Budapest International Research and Critics University, 2021)
The fundamental essence of a country born by a nation is bound by traditional values that crystallize in philosophy and have existed long before the country was founded. It must refer to the traditional values of the country. Indonesia has significant problems as well, also, with a series of complications and distortions in formulating nominations for solutions to each situation. The philosophy that becomes the reference and the fundamental values of the tradition is believed to solve these problems. If the philosophy of the convention is by religious values, only religion can subdue belief in the truth of traditional customs for the nation that was born. As a religion of rahmatan lil'alamin, Islam has a universal nature, meaning that Islamic teachings can cover all aspects of living. This research urgency is that the community, especially the Batak tribe, can revitalize their life orientation, including the exposure of building structures and infrastructure in line with the Poda Na Lima philosophy, by first finding the relevances between the things that are important to them in their status as Muslims and Bataks. The method used in this study is a qualitative method using a critical discourse analysis approach. From the presentation of the results of this study, it is apparent that the five points of Poda Nalima contain teachings and education that have extraordinary values and become a philosophy and rule of life in society. The whole of the contents of the Poda na lima is in line with and relevant to the teachings of Islam.